Chemical characterization and antioxidant activities of oligomeric and polymeric procyanidin fractions from grape seeds - Spranger, Isabel (2008)
Two procyanidin fractions, namely oligomers and polymers isolated from grape seed methanolic extract were characterized. Phenolic composition and procyanidin purity of these fractions were determined by normal-phase and reverse-phase HPLC, thioacidolysis-HPLC, ESI-MS analyses, formaldehyde–HCl precipitation and elemental analysis. Antioxidant activities of these fractions and other wellknown antioxidants were measured using xanthine–xanthine oxidase system for generating superoxide radical (O 2 ), the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical method and the Fenton system for generating hydroxyl radical (HO ). The results showed that both oligomeric and polymeric procyanidin fractions were highly pure, with the degree of polymerization ranging from 2 to 17–18 and 12 to 32–37, respectively. On the basis of molar concentration, polymeric procyanidins appeared the highest antioxidant activities, followed by oligomeric procyanidins, whereas catechins presented a lower antioxidant activity than its oligomers and polymers. These results indicate that the antioxidant activities of grape seed procyanidins are positively related to their degree of polymerization. Moreover, grape seed procyanidins presented higher antioxidant activities than other well-known antioxidants such as vitamin C, suggesting that grape seed procyanidins might be of interest to be used as alternative antioxidants